Annual review of phytopathology. - Cook, R. James (Palo Alto, Calif. : Annual Reviews, Inc., 1963)
Publishes original critical reviews of the significant literature and current developments in phytopathology.
Vol. 24 (1986; vi, 530 p.) ; Vol. 25 (1987; ix, 460 p.) ; Vol. 26 (1988; viii, 493 p.) ; Vol. 27 (1989; vii, 641 p.) ; Vol. 28 (1990; vii, 493 p.) ; Vol. 29 (1991; viii, 516 p.)
Eds. vol. 24-29 : R. James Cook ... et al.
Keywords: Plant diseases; Plant diseases -- Research; Plant diseases; Biology